Implementation Model of Equity Participation in Regional Development Banks in Indonesia - Susanti, Elian; Nurazi, Ridwan; Fachruzzaman, Fachruzzaman; Saiful, Saiful; Hardinata, Dodi (International Review of Management and Marketing, 2022)
The purpose of this study is to analyze the implementation of competitive advantage in equity participation in PT Bank Pembangunan Daerah for the period of October 2020 which is still in the category of Commercial Banks Based on Business Activities 1. Specifically, this research also tries to build the best implementation model for regional capital participation to PT Bank Pembangunan Daerah which is integrated with the planning and budgeting system and integrated with regional development priorities. We operate qualitative method which aims to get the real picture by developing a process analysis using direct data sources from informants totaling 27 people with very competent status in the field of regional capital participation at PT Bank Pembangunan Daerah Bengkulu Province and Central Sulawesi Province. Creswell (2009) states that the research process involves questions and procedures that arise, data that is usually collected in a participant setting, data analysis that is constructed inductively from specific to general themes. The results of the study explain that competitive advantage is seen from the substance of the low cost strategy of 25 (twenty five) Regional General Treasurers as Regional Financial Management Officers, there are 20 (twenty) Regional General Treasurers as Regional Financial Management Officers stating that the implementation of competitive advantage is seen from the substance the low-cost strategy is still not optimal (80% of informants), and 5 (five) Regional General Treasurers as Regional Financial Management Officers explain that currently there is no implementation of the low-cost strategy in the series of processes for capital participation in the work area carried out by PT Bank Pembangunan Daerah Bengkulu and in the work area of PT Bank Pembangunan Daerah Sulawesi Tengah (20% Informants). The best implementation model to build the integration of the provincial/district/city government capital participation system into PT Bank Pembangunan Daerah in an optimal and regulatory manner with operations is: Phase 1, capital participation management is integrated with regional regulations on RPJMD, Restra SKPD documents, and RKPD documents. Stage 2, the management of equity participation is implemented in regional regulations concerning APBD, then realized and evaluated in the general meeting of shareholders and/or other coordination meetings.